THE INFLUENCE OF SPEED ENDURENCE, LEG LENGTH, AND ACHIEVEMENT MOTIVATION ON THE ACHIEVEMENT OF INDONESIAN JUNIOR TAEKWONDO ATHLETES IN 2023 - Mugiyanto; Fachrezzy, Fahmy; Subandi, Oman Unju (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
The purpose of this study was to determine and reveal whether or not there is an influence between speed endurance, leg length, and achievement motivation on the achievement of Indonesian taekwondo junior athletes in 2023. This research was carried out using a quantitative approach using the survey method with path analysis techniques. The population in this study were all Indonesian taekwondo junior athletes. By taking the sample using the total sampling technique where the sample used is all of the population, namely all members of Indonesian junior taekwondo athletes because in the research that will be carried out because the population is considered smaller or less than 100. Based on the results of data analysis and hypothesis testing from research data variable speed endurance, leg length, motivation and achievement results of Indonesian taekwondo junior athletes, the following conclusions can be drawn: There is an effect of speed endurance on motivation with a direct influence percentage of 49.3%. There is an effect of leg length on motivation with a direct influence percentage of 39.5%. There is an effect of speed endurance on the achievement results of Indonesian junior taekwondo athletes with a direct influence percentage of 21.3%. There is an effect of leg length on the achievement of Indonesian junior taekwondo athletes with a direct influence percentage of 19.9%. There is a motivational influence on the achievement of Indonesian junior taekwondo athletes with a direct influence percentage of 58%. There is an indirect effect between speed endurance on the achievement results of Indonesian junior taekwondo athletes through motivation with a significance value of 0.468. There is an indirect effect between leg length on the achievement of Indonesian junior taekwondo athletes through motivation with a significance value of 0.428.